Relative age effects in women's Rugby Union from developmental leagues to World Cup tournaments - Lemez, S.; MacMahon, C.; Weir, P. (Research Quarterly for Exercise and Sport, 2016)
Annual age cohort groupings promote relative age effects (RAEs), which often, inadvertently, create participation and attainment biases between relatively older and younger players within the same age cohort. In a globally evolving sport, women's rugby team selection practices may potentially bypass qualified players as a result of maturational differences. Purpose: Our study examined the prevalence of RAEs in women's rugby union. Method: Player data (age range = 4-21+ years) were gathered from the 2006 and 2010 Rugby World Cups (n = 498) and from Canadian (n = 1,497) and New Zealand (NZ; n = 13,899) developmental rugby leagues. Results: Although no evidence of an RAE was found in the World Cup samples, chi-square analyses identified some typical and atypical patterns of RAEs at the developmental levels (w = .3). Younger developmental groups displayed a typical RAE patterning with a greater representation of older players (Canadian 13-year-olds, w = .58; NZ 4-year-olds, w = .35), whereas older developmental groups displayed an atypical RAE patterning with a greater representation of younger players (Canadian 19-year-olds, w = .58; NZ 17-year-olds, w = .32). Further, a traditional RAE emerged in the Canadian 11- to 15-year-old age group, ?2(3) = 10.92, p < .05, w = .30. Conclusion: The lack of homogeneity of traditional RAEs across the sample questions the existence of a single, clear RAE in women's rugby. Some evidence of participation inequalities at the developmental levels suggests that further RAE research in more varied sociocultural contexts may be necessary.